Muá¸¥Äsabah Al-Qur'an: Penafsiran dan Penerapannya sebagai Self-Healing Manusia Modern - Zainal Muttaqin; Amaliatus Solikhah Solikhah; Desty Rahmawati Rahmawati; Ach. Shodiqil Hafil (Indonesian Journal of Humanities and Social Sciences, 2023)
This article discusses the concept of muá¸¥Äsabah in the Qur'an and its relevance as a self-healing tool for modern humans. The concept of muá¸¥Äsabah refers to self-introspection, evaluation, and consideration of one's actions and behavior. In the context of the Qur'Än, muá¸¥Äsabah is an important concept that teaches individuals to reflect on their actions, identify mistakes, and improve themselves. This article profoundly reviews Qur'anic verses emphasizing the importance of muá¸¥Äsabah in daily life. In addition, the article also discusses its relevance in the context of modern society, which often faces stress, anxiety, and mental well-being issues. Through a deep understanding of the concept of muá¸¥Äsabah, modern man can use it as a self-healing tool to overcome various mental and emotional challenges. This article will explain how muá¸¥Äsabah can help individuals develop self-awareness, improve quality of life, and achieve better well-being. By blending religious insights and modern psychology, this article illustrates how the concept of muá¸¥Äsabah in the Qur'Än can be a valuable guideline for self-healing and personal growth of modern man. The practical implications of this understanding are improved mental well-being, the establishment of healthier social relationships, and positive contributions to society as a whole.